FORMALIZATION OF THE LEVEL OF A CORPORATE MANAGEMENT WITH DUE CONSIDERATION OF AN IMPACT IT ON COMPANY VALUE - Nataliya A. Volkova (Statistika i Èkonomika, 2016)
The article discusses the problems of corporate management considering features of the Russian specifics. The great attention is focused on a relationship of corporate management and the company’s value in general. The comparison of indicators that satisfy the needs of investors and owners of a company is hold. Methods of valuations are compared. The authors offer the approach to quantitative assessment of corporate management quality taking into account the value of the corporation.